Have Bangladesh’s Polders Decreased Livelihood Vulnerability? A Comparative Case Study - Nath, Sanchayan; van Laerhoven, Frank; Driessen, Peter P. J. (Sustainability, 2019)
Communities living in coastal regions are vulnerable to flooding, salinity intrusion, and natural hazards. This is aggravated by climate change. In order to reduce this vulnerability, governments have invested heavily in developing coastal infrastructures. One type of infrastructure development regards polders (i.e., pieces of land previously subject to permanent or temporal overflow that are now surrounded by embankments that prevent inundation). The impact of polderization on livelihood vulnerability is not straightforward and is therefore still poorly understood. In order to analyze such impacts, we present a comparative case study of four polders in Bangladesh that are characterized by varying societal circumstances, hydrological conditions, hydrological interventions, and different levels of community response to polderization. How does livelihood vulnerability vary temporally and spatially in polders, and what explains such variation? We use data collected via 162 surveys, 40 semi-structured interviews, and secondary research to analyze trends in the scores of the livelihood vulnerability index. Based on our analysis, we argue that after accounting for interactions amongst variables like hydrological conditions, hydrological interventions, community response, and other societal factors, livelihood vulnerability is lower in polders characterized by higher community involvement in using hydrological interventions to control the flow of saline water.